Tax Planning in Transition: Evaluating the Impact of Evolving Legislation on Financial Strategies - Puspita, Tika (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This research investigates the dynamics of tax planning amidst legislative changes and transitions in the modern tax environment, focusing on the interaction between tax law changes, economic dynamics, and strategic tax planning. Research Design and Methodology: This research design adopts qualitative analysis to explore various dimensions of tax planning, including economic, political, ethical, and strategic perspectives. Findings and Discussion: The findings suggest that tax planning is multifaceted, with the importance of constantly monitoring legislative changes, cross-disciplinary collaboration, and proactive strategic management. Implications: The research emphasizes that effective tax planning requires an approach responsive to regulatory change and integration with broader financial objectives.